Short Communication: Genetic resources of fast-growing tree for rehabilitating upland area of deteriorated Saguling catchment, West Java, Indonesia - HENTI HENDALASTUTI RACHMAT; ATOK SUBIAKTO; ARIDA SUSILOWATI (Society for Indonesian Biodiversity, 2019)
Rachmat HH, Subiakto A, Susilowati A. 2019. Title. Short Communication: Genetic resources of fast-growing tree for rehabilitating upland area of deteriorated Saguling catchment, West Java, Indonesia Biodiversitas 20: 442-447. Representing the upper landscapes area in West Bandung District, West Java Province, Indonesia with the highest point of ± 650 m, Saguling reservoir covers catchment area of about ± 2300 ha. Many huge reservoirs in Indonesia experienced faster-observed sedimentation than those of its expected time. The main cause for this situation is that the sedimentation rate has been doubled or even more than that of calculated or expected. The phenomenon of excessive and accelerated sedimentation condition in a water reservoir indicated that the development of both areas and its community have neglected the conservation aspect of the catchment areas. Those, rehabilitation of catchment area become an urgent need. Related to rehabilitation purposes, we planted six fast-growing tree species (Ochroma pyramidale/balsa, Nauclea orientalis/gempol, Ficus variegate/nyawai, Antocephalus cadamba/jabon putih, Anthocephalus macrophyllus/jabon merah, and Octomeles sumatrana/binuang bini) to determine which ones were the most suitable for scale-up plantation in rehabilitation activities. Planting was designed by total planting in uniform planting distance of 3 x 3 m, each species planted in line planting technique consisted of 3 block replications. Measurement on seedling height was conducted over all species at 6 and 12 months after planting. The best height increment showing the fastest growing species at 6 months after planting then scaled up to bigger experimental plot covering 3 ha area. Of the sixth month after planting measurement, result showed balsa gained the highest average height (136.19 cm) followed by nyawai, binuang bini, jabon merah, jabon putih and gempol (133.53 cm, 99.60 cm, 78.27 cm, 70.60 cm, and 53..30 cm). Scaled up experimental plot for balsa showed the average height at 1.5, 2.5 and 3.5 year after planting (yap) was 4.16 m, 12.13 m, and 23.08 m while the average diameter breast height (DBH) was 7.0 cm, 20.14 cm and 28.21 cm. From study result, we suggested balsa as potential fast growing tree species planted for rehabilitation activities in Saguling catchment area.